A silicone-modified polyurethane sealant
Patent Information
- Application Number
- CN202310451243.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-24
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2043-04-24
AI Technical Summary
[0003]针对上述情况,为克服现有技术之缺陷,本发明之目的是提供一种有机硅改性聚氨酯密封胶,本发明提供的有机硅改性聚氨酯密封胶能在一定程度上保留聚氨酯密封胶和硅酮密封胶的优点,实现一定的互补,应用会更加广泛,成本低,有良好的应用前景,可有效解决现有技术中聚氨酯密封胶、硅酮密封胶制备成本高、使用效果差、应用受限的问题
[0019]This invention is scientifically sound, uses abundant raw materials, is environmentally friendly, pollution-free, and easy to produce. It utilizes a "click" reaction to design silane end-capping agents for polyurethane modification, creating an organosilicon-modified polyurethane sealant for bonding substrates. This sealant exhibits strong thermal stability, high tensile strength, excellent adhesion, and resistance to bubbling in damp conditions. The sealant is inexpensive and provides good adhesion to materials such as glass and PVC. It does not generate bubbles during curing, ensuring airtightness at the application site. It releases very few harmful substances during curing, demonstrating excellent environmental friendliness. It does not contain free isocyanate monomers, posing no health or safety risks during operation and use. With promising application prospects, this innovative sealant preparation offers significant economic and social benefits.
Smart Images

Figure CN117384579B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to polymer materials, and in particular to an organosilicon-modified polyurethane sealant. Background Technology
[0002] Polyurethane (PU) sealants and silicone (SR) sealants have wide applications. PU sealants are polymers composed of hard and soft segments, containing -NHCOO- bonds in their molecules. PU sealants have advantages such as high strength and good elasticity, but they are prone to bubbling during curing and require a long time to fully cure. Furthermore, a primer is sometimes required on metal and glass materials, increasing the complexity of application. SR sealants have good weather resistance, but their surface is difficult to finish, and the production process of SR sealant raw materials is energy-intensive. Silane-modified polyurethane sealants combine the advantages of both PU and SR sealants and have wide applications. Therefore, providing a low-cost, environmentally friendly, easy-to-use, and effective silicone-modified polyurethane sealant is a crucial technical problem that must be solved. Summary of the Invention
[0003] In view of the above situation and to overcome the defects of the prior art, the purpose of this invention is to provide a silicone-modified polyurethane sealant. The silicone-modified polyurethane sealant provided by this invention can retain the advantages of polyurethane sealant and silicone sealant to a certain extent, achieve a certain degree of complementarity, have a wider range of applications, low cost, and good application prospects. It can effectively solve the problems of high preparation cost, poor performance and limited application of polyurethane sealant and silicone sealant in the prior art.
[0004] The technical solution provided by this invention is an organosilicon-modified polyurethane sealant, comprising the following components by weight: 23-27 parts of silane-modified polyurethane prepolymer, 40-50 parts of filler, 2.7-3.3 parts of silane crosslinking agent, 0.8-1.2 parts of first catalyst, 0.8-1.2 parts of dehydrating agent, 23-27 parts of plasticizer, 0.4-0.6 parts of ultraviolet light absorber, and 0.4-0.6 parts of light stabilizer;
[0005] The preparation method is as follows: 1. Mix silane-modified polyurethane prepolymer and plasticizer in a reaction vessel, stir and react for 10 min at 2000 r / min and 25℃, and degas the resulting mixture in a vacuum degassing machine;
[0006] 2. Add filler, silane crosslinking agent, dehydrating agent, ultraviolet light absorber and light stabilizer to the reaction vessel, stir and react for 10 min at 600 r / min and 25℃, and degas the resulting mixture in a vacuum degassing machine;
[0007] 3. Add the first catalyst to the reactor, and stir the mixture at 600 r / min and 25℃ for 10 min under nitrogen protection to obtain the sealant;
[0008] The silane-modified polyurethane prepolymer is prepared by the following steps:
[0009] 1. Preparation of silane coupling agents:
[0010] Mercaptopropyltrimethoxysilane and hydroxyethyl methacrylate were added to a first container equipped with a thermometer and a stirrer. Azobisisobutyronitrile (AIBN) was added to the first container. The mixture was stirred at 80-85°C and 510 r / min for 30-40 min. The content of -C=C- groups was measured every 10 min. The reaction was stopped when the content of -C=C- groups was 0, and the silane coupling agent was obtained.
[0011] The weight ratio of mercaptopropyltrimethoxysilane, hydroxyethyl methacrylate, and azobisisobutyronitrile is 9.815:6.507:0.082.
[0012] 2. Preparation of polyurethane prepolymer:
[0013] The vacuum-dehydrated polyether polyol and isoflurane diisocyanate were added to a second container equipped with a thermometer and a stirrer. Two drops of the second catalyst were added. Under nitrogen protection, the mixture was stirred and reacted at 80°C and 200 r / min for 3-4 hours. The content of -NCO groups was measured every 0.5 hours. When the content of -NCO groups remained unchanged, the reaction was stopped to obtain the polyurethane prepolymer.
[0014] The weight ratio of the polyether polyol to isoflurane diisocyanate is 80:4.5.
[0015] 3. Preparation of silane-modified polyurethane prepolymer:
[0016] The prepared silane coupling agent was added to the prepared polyurethane prepolymer and reacted at 80℃ and 200r / min for 14-15h. The -NCO group content was measured every 2h. When the -NCO group content was 0, the reaction ended and the silane-modified polyurethane prepolymer was obtained.
[0017] The molar ratio of the silane coupling agent to the polyurethane prepolymer is 1.05:1.
[0018] The filler is nano-calcium carbonate filler. Nano-calcium titanate is placed in an oven at 120°C for no less than 12 hours, then removed and allowed to cool naturally to obtain a moisture-free nano-calcium carbonate filler.
[0019] This invention is scientifically sound, uses abundant raw materials, is environmentally friendly, pollution-free, and easy to produce. It utilizes a "click" reaction to design silane end-capping agents for polyurethane modification, creating an organosilicon-modified polyurethane sealant for bonding substrates. This sealant exhibits strong thermal stability, high tensile strength, excellent adhesion, and resistance to bubbling in damp conditions. The sealant is inexpensive and provides good adhesion to materials such as glass and PVC. It does not generate bubbles during curing, ensuring airtightness at the application site. It releases very few harmful substances during curing, demonstrating excellent environmental friendliness. It does not contain free isocyanate monomers, posing no health or safety risks during operation and use. With promising application prospects, this innovative sealant preparation offers significant economic and social benefits.
[0020] Instruction manual illustrations
[0021] Figure 1 This is a diagram illustrating the reaction mechanism of the present invention.
[0022] Figure 2 A graph showing the relationship between tensile strength and elongation at break of the silicone-modified polyurethane sealant provided by this invention.
[0023] Figure 3 The diagram showing the relationship between shear strength and displacement of the silicone-modified polyurethane sealant provided by this invention. Detailed Implementation
[0024] The specific implementation of the present invention will be described in detail below with reference to examples and specific circumstances.
[0025] Example 1
[0026] An organosilicon-modified polyurethane sealant is made from the following components by weight: 23 parts of silane-modified polyurethane prepolymer, 40 parts of filler, 2.7 parts of silane crosslinking agent, 0.8 parts of first catalyst, 0.8 parts of dehydrating agent, 23 parts of plasticizer, 0.4 parts of ultraviolet light absorber, and 0.4 parts of light stabilizer.
[0027] The preparation method is as follows: 1. Mix silane-modified polyurethane prepolymer and plasticizer in a reaction vessel, stir and react for 10 min at 2000 r / min and 25℃, and degas the resulting mixture in a vacuum degassing machine;
[0028] 2. Add filler, silane crosslinking agent, dehydrating agent, ultraviolet light absorber and light stabilizer to the reaction vessel, stir and react for 10 min at 600 r / min and 25℃, and degas the resulting mixture in a vacuum degassing machine;
[0029] 3. Add the first catalyst to the reactor, and stir the mixture at 600 r / min and 25℃ for 10 min under nitrogen protection to obtain the sealant;
[0030] The silane-modified polyurethane prepolymer is prepared by the following steps:
[0031] 1. Preparation of silane coupling agents:
[0032] Mercaptopropyltrimethoxysilane and hydroxyethyl methacrylate were added to a first container equipped with a thermometer and a stirrer. Azobisisobutyronitrile (AIBN) was added to the first container. The mixture was stirred at 80-85°C and 510 r / min for 30-40 min. The content of -C=C- groups was measured every 10 min. The reaction was stopped when the content of -C=C- groups was 0, and the silane coupling agent was obtained.
[0033] The weight ratio of mercaptopropyltrimethoxysilane, hydroxyethyl methacrylate, and azobisisobutyronitrile is 9.815:6.507:0.082.
[0034] 2. Preparation of polyurethane prepolymer:
[0035] The vacuum-dehydrated polyether polyol and isoflurane diisocyanate were added to a second container equipped with a thermometer and a stirrer. Two drops of the second catalyst were added. Under nitrogen protection, the mixture was stirred and reacted at 80°C and 200 r / min for 3-4 hours. The content of -NCO groups was measured every 0.5 hours. When the content of -NCO groups remained unchanged, the reaction was stopped to obtain the polyurethane prepolymer.
[0036] The weight ratio of the polyether polyol to isoflurane diisocyanate is 80:4.5.
[0037] 3. Preparation of silane-modified polyurethane prepolymer:
[0038] The prepared silane coupling agent was added to the prepared polyurethane prepolymer and reacted at 80℃ and 200r / min for 14-15h. The -NCO group content was measured every 2h. When the -NCO group content was 0, the reaction ended and the silane-modified polyurethane prepolymer was obtained.
[0039] The molar ratio of the silane coupling agent to the polyurethane prepolymer is 1.05:1.
[0040] The filler is nano-calcium carbonate filler. Nano-calcium titanate is placed in an oven at 120°C for no less than 12 hours, then removed and allowed to cool naturally to obtain a moisture-free nano-calcium carbonate filler.
[0041] Example 2
[0042] An organosilicon-modified polyurethane sealant is made from the following components by weight: 27 parts of silane-modified polyurethane prepolymer, 50 parts of filler, 3.3 parts of silane crosslinking agent, 1.2 parts of first catalyst, 1.2 parts of dehydrating agent, 27 parts of plasticizer, 0.6 parts of ultraviolet light absorber, and 0.6 parts of light stabilizer.
[0043] The preparation method is as follows: 1. Mix silane-modified polyurethane prepolymer and plasticizer in a reaction vessel, stir and react for 10 min at 2000 r / min and 25℃, and degas the resulting mixture in a vacuum degassing machine;
[0044] 2. Add filler, silane crosslinking agent, dehydrating agent, ultraviolet light absorber and light stabilizer to the reaction vessel, stir and react for 10 min at 600 r / min and 25℃, and degas the resulting mixture in a vacuum degassing machine;
[0045] 3. Add the first catalyst to the reactor, and stir the mixture at 600 r / min and 25℃ for 10 min under nitrogen protection to obtain the sealant;
[0046] The silane-modified polyurethane prepolymer is prepared by the following steps:
[0047] 1. Preparation of silane coupling agents:
[0048] Mercaptopropyltrimethoxysilane and hydroxyethyl methacrylate were added to a first container equipped with a thermometer and a stirrer. Azobisisobutyronitrile (AIBN) was added to the first container. The mixture was stirred at 80-85°C and 510 r / min for 30-40 min. The content of -C=C- groups was measured every 10 min. The reaction was stopped when the content of -C=C- groups was 0, and the silane coupling agent was obtained.
[0049] The weight ratio of mercaptopropyltrimethoxysilane, hydroxyethyl methacrylate, and azobisisobutyronitrile is 9.815:6.507:0.082.
[0050] 2. Preparation of polyurethane prepolymer:
[0051] The vacuum-dehydrated polyether polyol and isoflurane diisocyanate were added to a second container equipped with a thermometer and a stirrer. Two drops of the second catalyst were added. Under nitrogen protection, the mixture was stirred and reacted at 80°C and 200 r / min for 3-4 hours. The content of -NCO groups was measured every 0.5 hours. When the content of -NCO groups remained unchanged, the reaction was stopped to obtain the polyurethane prepolymer.
[0052] The weight ratio of the polyether polyol to isoflurane diisocyanate is 80:4.5.
[0053] 3. Preparation of silane-modified polyurethane prepolymer:
[0054] The prepared silane coupling agent was added to the prepared polyurethane prepolymer and reacted at 80℃ and 200r / min for 14-15h. The -NCO group content was measured every 2h. When the -NCO group content was 0, the reaction ended and the silane-modified polyurethane prepolymer was obtained.
[0055] The molar ratio of the silane coupling agent to the polyurethane prepolymer is 1.05:1.
[0056] The filler is nano-calcium carbonate filler. Nano-calcium titanate is placed in an oven at 120°C for no less than 12 hours, then removed and allowed to cool naturally to obtain a moisture-free nano-calcium carbonate filler.
[0057] Example 3
[0058] An organosilicon-modified polyurethane sealant is made from the following components by weight: 25 parts of silane-modified polyurethane prepolymer, 45 parts of filler, 3 parts of silane crosslinking agent, 1 part of first catalyst, 1 part of dehydrating agent, 25 parts of plasticizer, 0.5 parts of ultraviolet light absorber, and 0.5 parts of light stabilizer.
[0059] The preparation method is as follows: 1. Mix silane-modified polyurethane prepolymer and plasticizer in a reaction vessel, stir and react for 10 min at 2000 r / min and 25℃, and degas the resulting mixture in a vacuum degassing machine;
[0060] 2. Add filler, silane crosslinking agent, dehydrating agent, ultraviolet light absorber and light stabilizer to the reaction vessel, stir and react for 10 min at 600 r / min and 25℃, and degas the resulting mixture in a vacuum degassing machine;
[0061] 3. Add the first catalyst to the reactor, and stir the mixture at 600 r / min and 25℃ for 10 min under nitrogen protection to obtain the sealant;
[0062] The silane-modified polyurethane prepolymer is prepared by the following steps:
[0063] 1. Preparation of silane coupling agents:
[0064] Mercaptopropyltrimethoxysilane and hydroxyethyl methacrylate were added to a first container equipped with a thermometer and a stirrer. Azobisisobutyronitrile (AIBN) was added to the first container. The mixture was stirred at 80-85°C and 510 r / min for 30-40 min. The content of -C=C- groups was measured every 10 min. The reaction was stopped when the content of -C=C- groups was 0, and the silane coupling agent was obtained.
[0065] The weight ratio of mercaptopropyltrimethoxysilane, hydroxyethyl methacrylate, and azobisisobutyronitrile is 9.815:6.507:0.082.
[0066] 2. Preparation of polyurethane prepolymer:
[0067] The vacuum-dehydrated polyether polyol and isoflurane diisocyanate were added to a second container equipped with a thermometer and a stirrer. Two drops of the second catalyst were added. Under nitrogen protection, the mixture was stirred and reacted at 80°C and 200 r / min for 3-4 hours. The content of -NCO groups was measured every 0.5 hours. When the content of -NCO groups remained unchanged, the reaction was stopped to obtain the polyurethane prepolymer.
[0068] The weight ratio of the polyether polyol to isoflurane diisocyanate is 80:4.5.
[0069] 3. Preparation of silane-modified polyurethane prepolymer:
[0070] The prepared silane coupling agent was added to the prepared polyurethane prepolymer and reacted at 80℃ and 200r / min for 14-15h. The -NCO group content was measured every 2h. When the -NCO group content was 0, the reaction ended and the silane-modified polyurethane prepolymer was obtained.
[0071] The silane coupling agent and polyurethane prepolymer Moor ratio The ratio is 1.05:1.
[0072] The filler is nano-calcium carbonate filler. Nano-calcium titanate is placed in an oven at 120°C for no less than 12 hours, then removed and allowed to cool naturally to obtain a moisture-free nano-calcium carbonate filler.
[0073] Example 4:
[0074] An organosilicon-modified polyurethane sealant is made from the following components by weight: 23 parts of silane-modified polyurethane prepolymer, 50 parts of filler, 2.7 parts of silane crosslinking agent, 1.2 parts of first catalyst, 0.8 parts of dehydrating agent, 27 parts of plasticizer, 0.4 parts of ultraviolet light absorber, and 0.6 parts of light stabilizer.
[0075] The preparation method is as follows: 1. Mix silane-modified polyurethane prepolymer and plasticizer in a reaction vessel, stir and react for 10 min at 2000 r / min and 25℃, and degas the resulting mixture in a vacuum degassing machine;
[0076] 2. Add filler, silane crosslinking agent, dehydrating agent, ultraviolet light absorber and light stabilizer to the reaction vessel, stir and react for 10 min at 600 r / min and 25℃, and degas the resulting mixture in a vacuum degassing machine;
[0077] 3. Add the first catalyst to the reactor, and stir the mixture at 600 r / min and 25℃ for 10 min under nitrogen protection to obtain the sealant;
[0078] The silane-modified polyurethane prepolymer is prepared by the following steps:
[0079] 1. Preparation of silane coupling agents:
[0080] Mercaptopropyltrimethoxysilane and hydroxyethyl methacrylate were added to a first container equipped with a thermometer and a stirrer. Azobisisobutyronitrile (AIBN) was added to the first container. The mixture was stirred at 80-85°C and 510 r / min for 30-40 min. The content of -C=C- groups was measured every 10 min. The reaction was stopped when the content of -C=C- groups was 0, and the silane coupling agent was obtained.
[0081] The weight ratio of mercaptopropyltrimethoxysilane, hydroxyethyl methacrylate, and azobisisobutyronitrile is 9.815:6.507:0.082.
[0082] 2. Preparation of polyurethane prepolymer:
[0083] The vacuum-dehydrated polyether polyol and isoflurane diisocyanate were added to a second container equipped with a thermometer and a stirrer. Two drops of the second catalyst were added. Under nitrogen protection, the mixture was stirred and reacted at 80°C and 200 r / min for 3-4 hours. The content of -NCO groups was measured every 0.5 hours. When the content of -NCO groups remained unchanged, the reaction was stopped to obtain the polyurethane prepolymer.
[0084] The weight ratio of the polyether polyol to isoflurane diisocyanate is 80:4.5.
[0085] 3. Preparation of silane-modified polyurethane prepolymer:
[0086] The prepared silane coupling agent was added to the prepared polyurethane prepolymer and reacted at 80℃ and 200r / min for 14-15h. The -NCO group content was measured every 2h. When the -NCO group content was 0, the reaction ended and the silane-modified polyurethane prepolymer was obtained.
[0087] The molar ratio of the silane coupling agent to the polyurethane prepolymer is 1.05:1.
[0088] The filler is nano-calcium carbonate filler. Nano-calcium titanate is placed in an oven at 120°C for no less than 12 hours, then removed and allowed to cool naturally to obtain a moisture-free nano-calcium carbonate filler.
[0089] Both the first catalyst and the second catalyst are dibutyltin dilaurate.
[0090] The dehydrating agent is vinyltriethoxysilane.
[0091] The plasticizer is dioctyl phthalate.
[0092] The ultraviolet light absorber is Tinuvin 770.
[0093] The light stabilizer is Tinuvin 328.
[0094] The polyether polyol is a polyether diol.
[0095] The key technology of this invention is to use a "click" reaction to design a silane end-capping agent for modifying polyurethane, producing an organosilicon-modified polyurethane sealant for bonding substrates. This sealant has the advantages of strong thermal stability, high tensile strength, excellent bonding performance, and resistance to bubbling when exposed to moisture.
[0096] The tensile strength, elongation at break, surface drying time, and hardness of the silane-modified polyurethane sealant manufactured using the above examples, after curing for 7 days (thickness 1.5-2 mm) at approximately 25°C and 53% humidity, are shown in Table 1 below.
[0097] Table 1: Comparison of test performance results of the silicone-modified polyurethane sealant prepared in this invention, MS-JS-900 sealant, and Sibao 999 sealant:
[0098]
[0099] The test data in Table 1 clearly show that the silane-modified polyurethane sealant is superior to MS-JS-900 sealant and Sibao 999 sealant on the market in terms of tensile strength, elongation at break, shear strength, and surface drying time.
[0100] From the appendix Figure 2 It can be seen that the tensile strength of this sealant is 1.66 MPa and the elongation at break is 337%, which is superior to other types of sealants.
[0101] This sealant can bond various materials. As shown in the figure, it has good adhesion to glass, PVC, PA-6, and aluminum.
[0102] The sealant of this invention is inexpensive and has good adhesion to materials such as glass and PVC. It does not produce bubbles during the curing process, ensuring the airtightness of the application area. It releases very few harmful substances during curing, exhibiting excellent environmental friendliness. It does not contain free isocyanate monomers, so it will not cause harm to human health and safety during operation and use. It has good application prospects, represents an innovation in sealant preparation, and has significant economic and social benefits.
Claims
1. An organosilicon-modified polyurethane sealant, characterized in that: It is made from the following components by weight: 23-27 parts of silane-modified polyurethane prepolymer, 40-50 parts of filler, 2.7-3.3 parts of silane crosslinking agent, 0.8-1.2 parts of primary catalyst, 0.8-1.2 parts of dehydrating agent, 23-27 parts of plasticizer, 0.4-0.6 parts of ultraviolet light absorber, and 0.4-0.6 parts of light stabilizer; The preparation method is as follows: (1) Mix silane-modified polyurethane prepolymer and plasticizer in a reaction vessel, stir and react for 10 min at 2000 r / min and 25°C, and degas the resulting mixture in a vacuum degassing machine; (2) Add filler, silane crosslinking agent, dehydrating agent, ultraviolet light absorber and light stabilizer to the reaction vessel, stir and react for 10 min at 600 r / min and 25℃, and degas the resulting mixture in a vacuum degassing machine. (3) Add the first catalyst to the reactor, and stir for 10 min at 600 r / min and 25°C under nitrogen protection to obtain the sealant; The silane-modified polyurethane prepolymer is prepared by the following steps: (1) Preparation of silane coupling agents: Mercaptopropyltrimethoxysilane and hydroxyethyl methacrylate were added to a first container equipped with a thermometer and a stirrer. Azobisisobutyronitrile (AIBN) was added to the first container. The mixture was stirred at 80-85°C and 510 r / min for 30-40 min. The content of -C=C- groups was measured every 10 min. The reaction was stopped when the content of -C=C- groups was 0, and the silane coupling agent was obtained. The weight ratio of mercaptopropyltrimethoxysilane, hydroxyethyl methacrylate, and azobisisobutyronitrile is: 9.815:6.507:0.082; (2) Preparation of polyurethane prepolymer: The vacuum-dehydrated polyether polyol and isoflurane diisocyanate were added to a second container equipped with a thermometer and a stirrer. Two drops of the second catalyst were added. Under nitrogen protection, the mixture was stirred and reacted at 80°C and 200 r / min for 3-4 hours. The content of -NCO groups was measured every 0.5 hours. When the content of -NCO groups remained unchanged, the reaction was stopped to obtain the polyurethane prepolymer. The weight ratio of the polyether polyol to isoflurane diisocyanate is 80:4.
5. (3) Preparation of silane-modified polyurethane prepolymer: The prepared silane coupling agent was added to the prepared polyurethane prepolymer and reacted at 80℃ and 200r / min for 14-15h. The -NCO group content was measured every 2h. When the -NCO group content was 0, the reaction ended and the silane-modified polyurethane prepolymer was obtained. The molar ratio of the silane coupling agent to the polyurethane prepolymer is 1.05:
1.
2. The silicone-modified polyurethane sealant according to claim 1, characterized in that: It is made from the following parts by weight: 27 parts of silane-modified polyurethane prepolymer, 50 parts of filler, 3.3 parts of silane crosslinking agent, 1.2 parts of first catalyst, 1.2 parts of dehydrating agent, 27 parts of plasticizer, 0.6 parts of ultraviolet light absorber, and 0.6 parts of light stabilizer.
3. The silicone-modified polyurethane sealant according to claim 1, characterized in that: It is made from the following components by weight: 25 parts of silane-modified polyurethane prepolymer, 45 parts of filler, 3 parts of silane crosslinking agent, 1 part of first catalyst, 1 part of dehydrating agent, 25 parts of plasticizer, 0.5 parts of ultraviolet light absorber, and 0.5 parts of light stabilizer.
4. The silicone-modified polyurethane sealant according to claim 1, characterized in that: It is made from the following parts by weight: 23 parts of silane-modified polyurethane prepolymer, 50 parts of filler, 2.7 parts of silane crosslinking agent, 1.2 parts of first catalyst, 0.8 parts of dehydrating agent, 27 parts of plasticizer, 0.4 parts of ultraviolet light absorber, and 0.6 parts of light stabilizer.
5. The silicone-modified polyurethane sealant according to claim 1, characterized in that: Both the first catalyst and the second catalyst are dibutyltin dilaurate, and the filler is nano-calcium carbonate filler. Nano-calcium titanate is placed in an oven at 120°C for no less than 12 hours, then removed and cooled naturally to obtain a water-free nano-calcium carbonate filler.
6. The silicone-modified polyurethane sealant according to claim 1, characterized in that: The dehydrating agent is vinyltriethoxysilane.
7. The silicone-modified polyurethane sealant according to claim 1, characterized in that: The plasticizer is dioctyl phthalate.
8. The silicone-modified polyurethane sealant according to claim 1, characterized in that: The ultraviolet light absorber is Tinuvin 770.
9. The silicone-modified polyurethane sealant according to claim 1, characterized in that: The light stabilizer is Tinuvin 328.
10. The silicone-modified polyurethane sealant according to claim 1, characterized in that: The polyether polyol is a polyether diol.